Sequence variation in Plasmodium falciparum merozoite surface protein-2 is associated with virulence causing severe and cerebral malaria - Chaorattanakawee, Suwanna (PLoS One, 2018)
Parasite virulence, an important factor contributing to the severity of Plasmodium falciparum infection, varies among P. falciparum strains. Relatively little is known regarding markers of virulence capable of identifying strains responsible for severe malaria. We investigated the effects of genetic variations in the P.f. merozoite surface protein 2 gene (msp2) on virulence, as it was previously postulated as a factor. We analyzed 300 msp2 sequences of single P. falciparum clone infection from patients with uncomplicated disease as well as those admitted for severe malaria with and without cerebral disease. The association of msp2 variations with disease severity was examined. We found that the N allele at codon 8 of Block 2 in the FC27-like msp2 gene was significantly associated with severe disease without cerebral complications (odds ratio = 2.73, P = 0.039), while the K allele at codon 17 of Block 4 in the 3D7-like msp2 gene was associated with cerebral malaria (odds ratio = 3.52, P = 0.024). The data suggests possible roles for the associated alleles on parasite invasion processes and immune-mediated pathogenicity. Multiplicity of infection was found to associate with severe disease without cerebral complications, but not cerebral malaria. Variations in the msp2-FC27-block 2-8N and 3D7-block 4-17K allele appear to be parasite virulence markers, and may be useful in determining the likelihood for severe and cerebral malaria. Their interactions with potential host factors for severe diseases should also be explored.